2002
DOI: 10.1164/rccm.200206-503oc
|View full text |Cite
|
Sign up to set email alerts
|

Patient, Physician, and Family Member Understanding of Living Wills

Abstract: This study examines understanding of living wills by patients, family members, and physicians. Questionnaires were used to examine whether each cohort understood patients' living wills regarding endotracheal intubation and cardiopulmonary rescuscitation (CPR). Of 4,800 patients admitted during the study period, 206 reported having living wills, all of which precluded intubation and CPR for "terminal conditions." Of 140 admitted to the general hospital wards, 17 (12%) wanted their living wills to preclude intub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…1,4,37,38 Achieving this consensus is challenging, because a universal perception of hopelessness does not exist, and the concept of an ''abbreviated'' ICU trial (5-7 days) for critically ill patients with cancer is just entering the CCM lexicon. 17 Concomitantly, proxies do not have much faith in physicians' prognostication abilities 29,30,39,40 and may disagree among themselves or with their physicians even when faced with irrefutable evidence that death is imminent. 41,42 Finally, there is no legal accountability if a LW is ignored.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,37,38 Achieving this consensus is challenging, because a universal perception of hopelessness does not exist, and the concept of an ''abbreviated'' ICU trial (5-7 days) for critically ill patients with cancer is just entering the CCM lexicon. 17 Concomitantly, proxies do not have much faith in physicians' prognostication abilities 29,30,39,40 and may disagree among themselves or with their physicians even when faced with irrefutable evidence that death is imminent. 41,42 Finally, there is no legal accountability if a LW is ignored.…”
Section: Discussionmentioning
confidence: 99%
“…At the time they are approached to consider research participation, SDMs and family members may not know the patient's values and preferences [2] and may hold personal views regarding research that differ from the patient's [3]. A study involving hypothetical scenarios found that ICU survivors preferred consent for their research participation to be obtained from SDMs [4].…”
Section: Introductionmentioning
confidence: 99%
“…It not only affects health care personnel but the lay public as well. Patients and families are often under the impression that a living will is to be utilized to preclude treatment regardless of reason or cause (14). However, confusion surrounding DNR is not a provincial phenomenon and has afflicted health care for two decades, as first reported by Eisendrath and Jonsen (1983) (15).…”
Section: Discussionmentioning
confidence: 99%